Influence of respiratory rate on stroke volume variation in mechanically ventilated patients - De Backer, Daniel; Taccone, Fabio Silvio; Holsten, Roland; Ibrahimi, Fayssal; Vincent, Jean-Louis (Anesthesiology (Philadelphia), 2009)
Heart-lung interactions are used to evaluate fluid responsiveness in mechanically ventilated patients, but these indices may be influenced by ventilatory conditions. The authors evaluated the impact of respiratory rate (RR) on indices of fluid responsiveness in mechanically ventilated patients, hypothesizing that pulse pressure variation and respiratory variation in aortic flow would decrease at high RRs. In 17 hypovolemic patients, thermodilution cardiac output and indices of fluid responsiveness were measured at a low RR (14-16 breaths/min) and at the highest RR (30 or 40 breaths/min) achievable without altering tidal volume or inspiratory/expiratory ratio. An increase in RR was accompanied by a decrease in pulse pressure variation from 21% (18-31%) to 4% (0-6%) (P < 0.01) and in respiratory variation in aortic flow from 23% (18-28%) to 6% (5-8%) (P < 0.01), whereas respiratory variations in superior vena cava diameter (caval index) were unaltered, i.e., from 38% (27-43%) to 32% (22-39%), P = not significant. Cardiac index was not affected by the changes in RR but did increase after fluids. Pulse pressure variation became negligible when the ratio between heart rate and RR decreased below 3.6. Respiratory variations in stroke volume and its derivates are affected by RR, but caval index was unaffected. This suggests that right and left indices of ventricular preload variation are dissociated. At high RRs, the ability to predict the response to fluids of stroke volume variations and its derivate may be limited, whereas caval index can still be used.